Novel self-supported reduced graphene oxide foam-based CoAu electrode: An original anode catalyst for electrooxidation of borohydride in borohydride fuel cell. (November 2019) - Li, Biaopeng; Song, Congying; Zhang, Dongming; Ye, Ke; Cheng, Kui; Zhu, Kai; Yan, Jun; Cao, Dianxue; Wang, Guiling
Abstract: An original three-dimensional self-supported reduced graphene oxide (rGO) foam is successfully prepared in this work. This novel support material, modified with Co nanosheets and Au nanoparticles, is employed as a high-performance catalyst for NaBH4 electrooxidation under alkaline condition. The surface chemical component and morphology of the catalyst is characterized by X-ray diffraction pattern, X-ray photoelectron spectroscopy, scanning electron microscope. The synthesized electrode exhibits excellent performance (1.35 A cm −2 at 0 V) towards NaBH4 electrooxidation. The unique structure of rGO foam caused a large electrochemical active surface area (EASA(Au)  = 390 m 2  g −1 ), low electrochemical impedance, as well as 55.4% utilization efficiency of NaBH4 . Also, catalytic kinetic parameters during the electrooxidation reaction of NaBH4 in a low NaBH4 concentration are investigated. Results indicate that oxidation of BH4 − is a first-order reaction, and the exchanged number of electrons obtained at the CoAu/rGO foam electrode is 6.9. Finally, we practically apply it to a direct borohydride-hydrogen peroxide fuel cell (DBHPFC). This work suggests that the prepared rGO foam is an excellent current collector, and CoAu/rGO foam electrode is a promising anode catalyst to apply in DBHPFC. Graphical abstract: Image 1